Penggunaan Video Edukasi Menyikat Gigi terhadap Pengetahuan dan Keterampilan Pada Siswa Sekolah Dasar - Supriatna, Agus; Widyastuti, Nugraheni; Wahyudadi, Badai Septa; Rahmah, Nur Aulia (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2024)
Dental health education for school children is an effective strategy in preventing the occurrence of dental and oral diseases. Dental health education is a primary preventive measure carried out before a disease occurs. One effort that can be made to increase school children's knowledge and skills in brushing their teeth is by using audio-visual media. This media is not only effective in conveying information directly, but can also be used as an outreach tool that can be disseminated widely. The use of this technology can increase the audience's absorption and understanding, especially children who tend to be more responsive to visual media. The aim of this research was to determine the effect of using educational videos on brushing teeth on the knowledge and skills of Berbt Elementary School students. Muhammadiyah Berua, Makassar City. This type of research is quantitative research with a quasi-experimental approach. The sampling technique used was total sampling in all 6th grade classes at SD Berbt. Muhammadiyah II Berua has 36 students. Research Results Shows that the use of educational videos on brushing teeth significantly increases elementary school students' knowledge about the importance of maintaining oral health and the use of educational videos also significantly increases students' practical skills in brushing teeth.